Diseminasi Aturan Nasional Dan International Tentang Bullying Di SMA Yppk Teruna Bakti Waena-Jayapura-Papua - Farneubun, Petrus Kanisius; Setiawan, Aria Aditya (Journal Of Human And Education (JAHE), 2025)
Bullying has been a national and international concern. Most cases of bullying have taken place in schools, especially, among high school students. The United Nations, through International Convention on Children 1989, UNICEF, and Indonesian Ministry of Education Number 46/20023 have issued guidelines and regulations on how to prevent and address the cases of violence against children, including bullying in schools. The purpose of this community service is to raise high school students’ awareness and to educate them on various forms of bullying, the destructive impact of bullying and mechanism of reporting with reference to the national and international conventions. This community service is held in SMA YPPK Katolik Teruna Bakti, Waena, Jayapura. This school is selected because of its academic achievement, consistently maintaining A in its accreditation, and well-known for its high discipline. However, bullying still takes place in this school, with verbal and cyber forms of bullying the most. The method used in this program is presentation, discussion, and questions and answers. By the end of this program, students have an understanding of various dimensions of bullying, its impacts, and national and international guidelines on preventing and reporting bullying. It is recommended that the school to have anti bullying task force and a clear mechanism of reporting bullying. It is hoped that the school will be a role model for other schools to have similar program and free-bullying based school.